PENGEMBANGAN KURIKULUM PENDIDIKAN KARAKTER - Melinda, Puspita Ega; Nur Ahid; Rosa Deninta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education serves as a fundamental pillar in shaping a generation that excels not only intellectually but also in moral integrity and social responsibility. This article discusses the core principles, implementation strategies, curriculum development models, and the roles of key stakeholders in implementing character education in schools. A character-based curriculum must be designed based on relevance, sustainability, integration, and alignment with students’ socio-cultural context. Implementation strategies include intracurricular, extracurricular, and habituation activities within the school environment. Curriculum development is carried out through integrative, thematic, and hidden curriculum approaches aimed at comprehensive character formation. The active involvement of teachers, school leaders, parents, communities, and government is essential to creating an effective character education ecosystem. Teachers act as role models and facilitators, school leaders as transformative figures, parents as primary educators, and government as policy makers. Despite its importance, the implementation of character education faces various challenges, including limited teacher training, lack of integrated curricula, and weak stakeholder synergy. To address these issues, sustainable teacher training, stronger national policy support, and cross-sector collaboration are necessary. This article recommends enhancing the roles of all educational elements to ensure that character education moves beyond discourse into tangible practice, capable of forming morally strong and resilient generations to face the challenges of the 21st century.